2023
DOI: 10.3389/fphys.2023.1184651
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of the gene expression of M. iliotibialis lateralis affected by dietary methionine restriction

Abstract: Introduction: Methionine (Met) is an important amino acid related to the development of skeletal muscle. This study investigated the effects of dietary Met restriction on the gene expression of M. iliotibialis lateralis.Methods: A total of 84 day-old broiler chicks (Zhuanghe Dagu) with a similar initial body weight (207.62 ± 8.54 g) were used in this study. All birds were divided into two groups (CON; L-Met) based on the initial body weight. Each group consisted of six replicates with seven birds per replicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
(42 reference statements)
1
1
0
Order By: Relevance
“…Interestingly, our results showed that low TSAA/Lys ratio groups had better BW and FCR than middle and high TSAA/Lys ratio ones at 13 days and these were not significantly different from the recommended TSAA/Lys ratio even at 20 days . It has been confirmed in the native breed of broiler chicks (Zhuanghe Dagu) that dietary Met restriction (Met level was 80% of the control group) had no negative effects on body weight gain . The dietary AA balance affects the AA requirements of chickens.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Interestingly, our results showed that low TSAA/Lys ratio groups had better BW and FCR than middle and high TSAA/Lys ratio ones at 13 days and these were not significantly different from the recommended TSAA/Lys ratio even at 20 days . It has been confirmed in the native breed of broiler chicks (Zhuanghe Dagu) that dietary Met restriction (Met level was 80% of the control group) had no negative effects on body weight gain . The dietary AA balance affects the AA requirements of chickens.…”
Section: Discussionsupporting
confidence: 57%
“…5 It has been confirmed in the native breed of broiler chicks (Zhuanghe Dagu) that dietary Met restriction (Met level was 80% of the control group) had no negative effects on body weight gain. 27 The dietary AA balance affects the AA requirements of chickens. AAs could be effectively utilized when the various AAs in the diet are balanced.…”
Section: Discussionmentioning
confidence: 99%